Acute generalized exanthematous pustulosis provoked by furosemide - Andżelika Schwann-Majewska; Magdalena Lange; Aleksandra Wilkowska; Malwina Ornowska; Roman Nowicki (Termedia Publishing House, 2015)
Introduction. Acute generalized exanthematous pustulosis (AGEP) is a skin disease characterized by the sudden appearance of generalized pustules, accompanied by elevated body temperature and neutrophilia. Objective. Presentation of a patient with AGEP provoked by furosemide. Case report. We present a case of a 65-year-old patient diagnosed with and treated for generalized pustular eruption, with fever and changes in laboratory tests. Numerous coexisting medical conditions and a great number of frequently changed drugs (ciprofloxacin, allopurinol, folic acid, calcium carbonate, cyclophosphamide, atorvastatin, betaxolol and furosemide) hindered identification of the causative factor. Conclusions. On the basis of the medical history and clinical picture, the patient was diagnosed with generalized exanthematous pustulosis induced by furosemide.